2018
DOI: 10.1016/j.lrp.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents of new R&D collaborations with different partner types: On the dynamics of past R&D collaboration and innovative performance

Abstract: We examine firms' propensity to adapt their R&D collaboration portfolio by establishing new types of R&D collaboration with different kinds of partners (suppliers, customers, competitors and universities & public research institutions). We argue that existing R&D collaboration with one of the two value chain partners (suppliers or customers) is associated with the formation of new R&D collaboration with the other value chain partner to ensure temporal alignment in innovation within the value chain. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 117 publications
3
67
0
1
Order By: Relevance
“…These findings support previous work on the importance of R&D intensity and the skills and education of employees tasked with innovation [78,86,87,89]. Since the implementation of open innovation for sustainability requires specific organizational capacities and knowledge integration methods [46,61,78,90].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These findings support previous work on the importance of R&D intensity and the skills and education of employees tasked with innovation [78,86,87,89]. Since the implementation of open innovation for sustainability requires specific organizational capacities and knowledge integration methods [46,61,78,90].…”
Section: Discussionsupporting
confidence: 88%
“…It is confirmed that research-intensive companies with FDI are exporters, which avoids their research efforts benefiting the local economy rather than the global markets. Evidence of this is that the national cooperation network is not significant, but exports are [78,86,95].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cooperation in innovation has been identified as a valuable R&D strategy to complement the internal R&D efforts of firms (cf., e.g., Hofman, Faems, & Schleimer, 2017;Belderbos, Gilsing, Lokshin, Carree, & Sastre, 2018). Enterprises can cooperate with competitors in jointly exploiting existing products or technologies, to benefit from incremental innovations (Hofman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%